2006
DOI: 10.1158/0008-5472.can-05-1149
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin 2 Induces Glioma Cell Invasion by Stimulating Matrix Metalloprotease 2 Expression through the αvβ1 Integrin and Focal Adhesion Kinase Signaling Pathway

Abstract: Accumulating evidence reveals a significant correlation between angiopoietin 2 (Ang2) expression and tumor invasion and metastasis in various human cancers, but the major focus of recent studies has been on the angiogenic effects of Ang2. We recently reported that Ang2-stimulated glioma cell invasion results from the up-regulation and activation of matrix metalloprotease 2 (MMP-2) in tumor cells. In this study, we identify a novel mechanism by which Ang2 stimulates MMP-2 expression leading to glioma cell invas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 42 publications
8
116
1
Order By: Relevance
“…Our studies show that FAK is implicated in MMP-2 gene expression leading to increased MMP-2 secretion in SCC cells. Consistent with our findings, previous reports in v-Src transformed fibroblasts and glioma cells (Hauck et al, 2002;Hu et al, 2006) supported a role for FAK in promoting increased MMP-2 gene expression. This FAK signalling pathway also seems to operate in noncancerous cells (Segarra et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our studies show that FAK is implicated in MMP-2 gene expression leading to increased MMP-2 secretion in SCC cells. Consistent with our findings, previous reports in v-Src transformed fibroblasts and glioma cells (Hauck et al, 2002;Hu et al, 2006) supported a role for FAK in promoting increased MMP-2 gene expression. This FAK signalling pathway also seems to operate in noncancerous cells (Segarra et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The data revealed that, in accordance with the zymography analysis, MMP-2 and MMP-9 mRNA levels were, respectively, 62 and 85% lower in FRNK cells as compared with pWZL cells ( Figure 6D). These results are consistent with recent studies showing a positive role for FAK in mediating MMP-2 and MMP-9 secretion in other cell types (Sein et al, 2000;Hauck et al, 2002;Zhang et al, 2002;Hsia et al, 2003;Hu et al, 2006;.…”
Section: Inhibition Of Fak-mediated Signalling Pathway Impairs Cell Isupporting
confidence: 93%
See 1 more Smart Citation
“…U-87 MG cells transfected with Tie2 siRNA did not show a significant decrease in secreted VEGF in response to Ang2, suggesting that the regulation of VEGF by Ang2 is mediated by Tie2 (Figure 4b). Because several studies have shown that some of the functions of Angs require the presence of integrin b1 (Cascone et al, 2005;Hu et al, 2006), we assessed whether the presence of a neutralizing anti-integrin b1 antibody prevented the Ang2-mediated regulation of VEGF in glioma cells. As shown in Figure 4c, blocking integrin b1 did not rescue the effect of Ang2 on VEGF levels.…”
mentioning
confidence: 99%
“…Although strong evidence of an antiangiogenic role for Ang2 was obtained in transgenic animal models (Maisonpierre et al, 1997), other studies have shown that the overexpression of Ang2 in different tumors has a context-dependent antagonist function (Yancopoulos et al, 2000), including gliomas (Machein et al, 2004;Hu et al, 2006;Lee et al, 2006a). It is quite possible that the effect of Ang2 depends on differences in the VEGF levels (Goede et al, 1998;Holash et al, 1999;Beck et al, 2000).…”
mentioning
confidence: 99%